Mobile streaming of H.264 video over gilbert - elliotts channel - Baguda, Yakubu S. (World Academy of Science, Engineering and Technology, 2009)
Mobile multimedia applications are becoming increasingly popular in recent years due to explosive growth in demand for such services in both wired and wireless network. Undoubtedly, future wireless communication systems will eventually integrated a broad range of multimedia services such as voice, video, and data. Video applications play an extremely important role in surveillance, entertainment and remote monitoring. It is very obvious that achieving more reliable and efficient multimedia communication over wireless channel is challenging due to unpredictable channel condition, fading and multipath. In this paper, we investigate the impact of the channel condition on packet loss and percieve video quality. The scenario has been simulated and analysed base on Gilbert channel model, and it is primarily due to the fact it gives more realistic representation of the bursty channel such as wireless medium.